2021
DOI: 10.31234/osf.io/qv6fu
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pinging reveals active, not silent, working memories

Abstract: A hallmark of the ‘activity-silent’ working memory framework [1] is that memories stored silently in synaptic traces can be reactivated through non-specific stimuli [1–5]. Evidence supporting ‘activity-silent’ working memory has recently emerged from human electroencephalography (EEG) [6,7], in particular from ‘reactivations’ of unattended memories induced by visual impulses[7] - the so-called visual pinging. Here, we reanalyzed EEG recordings of this influential pinging study [7]. We found that unattended mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…We found that, in the activity-silent state, the most recently encoded stimulus was always encoded most strongly, even when it was a distractor. This may reflect involuntary encoding of irrelevant stimuli in a short-term synaptic memory trace (Barbosa et al, 2021(Barbosa et al, , 2020. This prediction should hold as the number of distractors is increased.…”
Section: Lesions To Areas With a High D1 Receptor Density Disrupt Working Memorymentioning
confidence: 97%
“…We found that, in the activity-silent state, the most recently encoded stimulus was always encoded most strongly, even when it was a distractor. This may reflect involuntary encoding of irrelevant stimuli in a short-term synaptic memory trace (Barbosa et al, 2021(Barbosa et al, , 2020. This prediction should hold as the number of distractors is increased.…”
Section: Lesions To Areas With a High D1 Receptor Density Disrupt Working Memorymentioning
confidence: 97%
“…While the information may not have been accessible with EEG or MEG measurements, it may have existed as spontaneous oscillations in the electrophysiological recordings (LaRocque et al, 2013;Foster et al, 2016). A recent reanalysis of the data shown in Wolff et al (2017) suggests this latter possibility (Barbosa et al, 2021). Finally, modeling has shown that observations of increased information content in IEM-based stimulus reconstructions following a task cue (Sprague et al, 2016) are not diagnostic of a transition from a passive to an active code (Schneegans and Bays, 2017).…”
Section: Mixed Selectivity In Pfcmentioning
confidence: 99%
“…For example, one experiment found that information about visual objects could be decoded from extrastriate visual areas on blocks of trials that required memory for visual details, but from PFC on blocks of trials where only the object's category had to be maintained (Lee et al, 2013). Other work has examined the effect of attentional priority on WM representational format, and has shown that high priority items tend to be represented more robustly than items that are not immediately relevant to behavior (Christophel et al, 2012;Lewis-Peacock, Drysdale, Oberauer, & Postle, 2012;Lorenc et al, 2020;Rose et al, 2016;Sprague, Ester, & Serences, 2016;Wolff, Jochim, Akyürek, & Stokes, 2017) (but see also Barbosa, Soldevilla, & Compte, 2021;Iamshchinina et al, 2021). Prioritized WM representations can be further reconfigured so that they are optimized for future behavior, which may include the activation of circuits related to motor output (Myers et al, 2017;Schneider, Barth, & Wascher, 2017;Souza & Oberauer, 2016;van Ede et al, 2019).…”
Section: Discussionmentioning
confidence: 99%